(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the educational opportunities of social networks in the context of foreign language education, focusing on the concept of foreign language information competence (FLIC) and its integration with communicative competence. The study discusses the types of social networks, their popularity among students and teachers, and the potential benefits of using social networks for teaching reading, writing, and other speech activities. The findings highlight the readiness of students and teachers to incorporate social networks into language learning, emphasizing their role in individualizing the learning process, increasing motivation, and reducing barriers to communication in a foreign language.